1999
DOI: 10.1159/000031131
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Antiglobulin Test: Still a Place for the Tube Technique?

Abstract: Objectives: Antibodies of different immunoglobulin isotypes, or complement, may coat red blood cells in vivo. They are detected by the direct antiglobulin test (DAT), usually performed by the conventional tube technique. The purpose of this study was to compare the latter technique with the gel test. Methods: Three hundred and ninety–eight consecutive samples, sent to our laboratory for direct antiglobulin testing, were analyzed with the tube technique and the gel test, using reagents from different manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
5
1
Order By: Relevance
“…This is consistent with several other studies that have found the DATs by GMA to be more sensitive than those tests performed by CTT at detecting red blood cell-bound IgG (9,21,22). Also, contrary to the results reported by Tissot et al (16), gel showed to be more sensitive at detecting C3d on red blood cells in our study. Moreover, the results of efficiency test calculations confirm that gel is superior to tube for DATs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is consistent with several other studies that have found the DATs by GMA to be more sensitive than those tests performed by CTT at detecting red blood cell-bound IgG (9,21,22). Also, contrary to the results reported by Tissot et al (16), gel showed to be more sensitive at detecting C3d on red blood cells in our study. Moreover, the results of efficiency test calculations confirm that gel is superior to tube for DATs.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors concluded that this technique is equal to or better than the CTT (9). On the other hand, Tissot et al (16) concluded that the GMA appeared to be less sensitive than the CTT when utilized for DATs.…”
Section: Introductionmentioning
confidence: 99%
“…Six weakpositive DAT were missed by DiaMed-ID ® and one was missed by using the conventional tube technique whereas only three were missed by DG Gel ® . It is important to point out that although there is a trend to replace conventional tube test by microtube gel tests (Lapierre et al, 1990), the former is still a widely used reference method (Tissot et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is not certain if either assay correlates with the clinical sequelae in these patients. When Tissot and colleagues 16 compared DATs with anti-C3d by tube agglutination and gel microcolumn assays, they found that tube agglutination assays were more likely to be reactive, but different sources of anti-C3d were used for the assays. They concluded that the tube agglutination assay was more sensitive for detection of RBC-bound C3d than gel microcolumn assays.…”
Section: Discussionmentioning
confidence: 99%